Abstract concepts, compositionality, and the contextualism-invariantism debate. (18th August 2017) - Löhr, Guido
Abstract: Invariantists argue that the notion of concept in psychology should be reserved for knowledge that is retrieved in a context-insensitive manner. Contextualists argue that concepts are to be understood in terms of context-sensitive ad hoc constructions. I review the central empirical evidence for and against both views and show that their conclusions are based on a common mischaracterization of both theories. When the difference between contextualism and invariantism is properly understood, it becomes apparent that the way the question of stability is currently investigated will not lead to a consensus. Instead of focusing directly on stability, we should turn our attention to other desiderata on a theory of concepts. In particular, I show that invariantism, but not contextualism, fails to account for compositionality and abstract concepts.